2008
DOI: 10.1002/dmrr.850
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of footwear and offloading interventions to prevent and heal foot ulcers and reduce plantar pressure in diabetes: a systematic review

Abstract: SummaryBackground Footwear and offloading techniques are commonly used in clinical practice for the prevention and treatment of foot ulcers in diabetes, but the evidence base to support this use is not well known. The goal of this review was to systematically assess the literature and to determine the available evidence on the use of footwear and offloading interventions for ulcer prevention, ulcer treatment, and plantar pressure reduction in the diabetic foot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
183
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(191 citation statements)
references
References 101 publications
3
183
0
5
Order By: Relevance
“…18,85 There also remain gaps in the knowledge about any benefit of potentially preventative interventions, such as patient education, routine podiatry, foot orthoses and specialist footwear. 84,[86][87][88] NICE recommends further research to identify the appropriate level and combination of risk factors used to categorise patients as being at high risk of ulceration and that these individuals should then be offered attendance on a protection programme. A UK-wide RCT to evaluate the clinical effectiveness and cost-effectiveness of such protection programmes is needed to evaluate the delivery of this type of health care.…”
Section: Secondary Analysesmentioning
confidence: 99%
“…18,85 There also remain gaps in the knowledge about any benefit of potentially preventative interventions, such as patient education, routine podiatry, foot orthoses and specialist footwear. 84,[86][87][88] NICE recommends further research to identify the appropriate level and combination of risk factors used to categorise patients as being at high risk of ulceration and that these individuals should then be offered attendance on a protection programme. A UK-wide RCT to evaluate the clinical effectiveness and cost-effectiveness of such protection programmes is needed to evaluate the delivery of this type of health care.…”
Section: Secondary Analysesmentioning
confidence: 99%
“…However, not all elderly patients or individuals with sedentary lifestyles sustain diabetic foot conditions. Studies have shown that proper diabetic control and proper foot care are vital for the overall prevention of diabetic foot conditions such as neuropathic ulcers, Charcot's arthropathy and lower limb infections (such as cellulitis, osteomyelitis and septic arthritis) (4)(5)(6)(7)(8). Improper prevention of diabetic foot conditions can result in significant morbidity, decreased function and quality of life (9).…”
Section: Introductionmentioning
confidence: 99%
“…In a lifetime, a person could cover, on his or her feet, a distance equal to more than 3 times the Earth's circumference. 1 Feet may be compromised by bacterial and fungal infections, 2-10 chronic disease, [10][11][12][13] obesity, 14 immune suppression, 9,10,15 vascular disease, 10,15 and uncomfortable or tight shoes. Tight shoes can injure the feet and make them prone to contamination and infections.…”
mentioning
confidence: 99%